PP.27.20: CARDIOVASCULAR REMODELLING IN MILD UNTREATED HYPERTENSIVE PATIENTS. (June 2015) - Test, L. Robustelli; Maresca, A.M.; Mongiardi, C.; Gadaleta, C.; Gessi, V.; Molaro, M.; Messina, P.; Moretti, S.; Agostinis, M.; Tandurella, N.; Tavecchia, L.; Bertolini, A.; et al.
Abstract : Objective: Uric acid (UA) may induce growth of cardiomyocytes and interstitial fibrosis in animal models. However, clinical studies that investigated the relationship between UA and cardiac and carotid remodelling showed conflicting results. So we evaluated the relationship between UA levels and morphofunctional biventricular and carotid parameters in a cohort of mild hypertensive untreated patients. Design and method: We enrolled 152 consecutive non-smoking patients, without known cardiovascular diseases, gout or diabetes, never treated with antihypertensive drugs: 88 subjects had newly diagnosed hypertension (BP > 130 and/or 80 mmHg during ABPM), 64 normotensive subjects matched for age, sex and body mass index. All patients underwent: blood tests with evaluation of acid uric levels and renal function parameters, echocardiography with left (LV) and right ventricle (RV) morphofunctional evaluation, carotid ultrasonography. Results: UA levels were higher in hypertensive patients (5.3 ± 1.4 vs 4.6 ± 1.2 mg/dL, p 0.003). Renal function was in normal range and similar in the two groups. Univariate analysis showed a relationship between UA and: LV mass (r 0.212, p 0.009), midwall fractional shortening (r -0.183 p 0.02), relative wall thickness (r 0.199 p 0.01), right ventricle wall thickness (r 0.303 p 0.001), RV E' (r -0.256 p 0.002), RV E/E' (r 0.176 p 0.03), carotid intima-media thickness (r 0.176 p 0.03). We found no correlation between UA and diastolic LV function parameters. Conclusions: In a cohort of mild hypertensive untreated patients, uric acid levels correlate with morphofunctional biventricular and carotid parameters. Our results may underline a role of uric acid in the onset of morphofunctional biventricular and carotid remodelling. New prospectives studies are needed to confirm these data.